INVESTIGATION OF NUMERICAL RANDOM SEQUENCE OBTAINED FROM WEB CAMERA - HANZHELO, DMYTRO; PROKHOROV, HEORHII (Herald of Khmelnytskyi National University. Technical sciences, 2024)
The investigation object of this paper is a random numbers sequence (RNS) obtained from a single frame of a webcam, which can be practically used as a source of chaos for a hardware RNS generator. The problem under consideration was to calculate the primary statistical characteristics of the RNS obtained from the webcam frame and compare them with the crypto-resistance requirements. The obtained statistics confirmed the hypothesis of a high level of chaos using a webcam. In successive frames from image capture (40 milliseconds gap), the photodiode matrix records changes that are not visible to the human eye. Even in absolute darkness , 60% of the changes in the brightness values of the matrix pixels are recorded. Which is 10% higher than the software engineering crypto-resistance requirements for the avalanche effect parameter. This is probably explained by the chaos that accompanies the stochastic interaction of photons of light with the atoms of the material of the sensor. Thus, it is possible to speak about a high level of chaos in the generated RNS. The peculiarity of the research is that for the purity of the experiment, frame generation was carried out in total darkness (approx. luminosity 10-4 lux), and a uniformly illuminated (luminosity 200 lux) white surface. Testing the web camera under extreme conditions gives a complete picture of the unpredictability and chaos of RNS generation. The primary investigation of the statistics of the generated RNS showed a good compliance with some crypto-resistance requirements. The method built on this property allows designing an affordable hardware RNS generator in laboratory conditions without the involvement of special equipment.